2018
DOI: 10.1007/s11064-018-2606-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Mexiletine with Novel Antiepileptic Drugs in the Maximal Electroshock Test in Mice: An Isobolographic Analysis

Abstract: The aim of the study was to evaluate precisely the type of interactions between mexiletine (an antiarrhythmic drug) and four new generation antiepileptic drugs: lamotrigine, oxcarbazepine, topiramate and pregabalin in the maximal electroshock test in mice (MES). The isobolographic analysis was used to assess the nature of interactions between the tested drugs. Total brain concentrations of antiepileptics were also measured to detect possible pharmacokinetic interactions. The results obtained indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Discontinuation of the relevant ASM or dose reduction is the preferred measure ( 71 ). Mesylate may be considered as an additional treatment to antiepileptic therapy, particularly for patients experiencing cardiac arrhythmias ( 72 ). Alternatively, new ASMs can be developed to achieve high effectiveness and safety ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discontinuation of the relevant ASM or dose reduction is the preferred measure ( 71 ). Mesylate may be considered as an additional treatment to antiepileptic therapy, particularly for patients experiencing cardiac arrhythmias ( 72 ). Alternatively, new ASMs can be developed to achieve high effectiveness and safety ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the FDA approved PER for use as monotherapy for focal epilepsy, PER showed favorable retention rates and safety profiles (68). Two meta-analyses of RCTs showed that PER had no arrhythmia-related adverse effects (69,70). However, the rates of other adverse reactions to PER are not extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a tendency towards antagonism was revealed for the combination of mexiletine and valproate in proportions of 1:1 and 3:1. Although the lowered brain concentration of valproate could be in part responsible for this result in the 1:1 proportion, no pharmacokinetic events were observed for the fixed ratios of 3:1 [ 24 , 25 ]. It can be suggested that a synergistic interaction occurred between mexiletine, a Nav1.5 and KCNH 2 antagonist and two antiepileptic drugs with different mexiletine mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth underlining that pharmacokinetic events may vary depending on the proportion of combined drugs. Mexiletine decreased the brain concentration of pregabalin at the dose ratio of 1:3, increased this level at 1:1, and did not alter it in the proportion of 3:1 [ 25 ].…”
Section: Antiarrhythmic Drugs Have Different Effects On Tonic–clonic ...mentioning
confidence: 99%
“…As has been reported, epilepsy has many common pathophysiological elements, together with arrhythmia, which may also suggest a relationship between antiarrhythmic and antiepileptic drugs (Wró blewska et al, 2018). Reports on the anticonvulsant activity of the cardiovascular drugs propranolol (Fischer et al, 1985;Fischer, 2002) and mexiletine (Chew et al, 1979) prompted many scientists to search for other aminoalkanol and/or aroxyalkyl derivatives possessing similar properties and functions.…”
Section: Introductionmentioning
confidence: 99%